Application of hyperbaric oxygen therapy in femoral head necrosis: a systematic review and meta-analysis - Yangbin Cao; Peiyuan Tang; Han Tan; Wenbo Ma; Hua Chai; Bin Lin; Ying Zhu; Wenfeng Xiao; Ting Wen; Jun Zhang; Yusheng Li; Shuguang Liu (EFORT Open Reviews)
Purpose: To evaluate the effectiveness of hyperbaric oxygen therapy (HBOT) in the treatment of osteonecrosis of the femoral head (ONFH). Methods: Search for term systems related to ONFH and HBOT in PubMed, Cochrane Library, Embase and Web of Science databases. The risk ratio (RR) was used as the effective index for dichotomous variables while mean difference (MD) and 95% confidence interval (CI) were used as the effective index for continuous variables, with a two-sided P < 0.05 considered statistically significant. I2 statistic and Q test were used to evaluate the statistical heterogeneity of the included studies. Results: Ten studies were included, involving 568 participants. Pre-post meta-analyses to show the visual analog scale after HBOT (MD = −2.94, 95% CI: −4.27, −1.60, P < 0.0001), short form 12 physical component summary scale (SF12 PCS) (MD = 17.28, 95% CI: 8.26, 26.31, P = 0.0002), short form 12 mental component summary scale (SF12 MCS) (MD = 4.26, 95% CI: 2.56, 5.95, P < 0.00001), Harris hip score (HHS) (MD = 26.91, 95% CI: 0.35, 53.46, P = 0.05), modified Harris hip score (mHHS) (MD = 44.31, 95% CI: 13.75, 74.87, P = 0.004) were significantly different from those before treatment. The results of SF12 PCS (MD = −0.39, 95% CI: −7.85, 7.06, P = 0.92) and SF12 MCS (MD = 0.76, 95% CI: −7.02, 8.52, P = 0.85), patients’ improved events (RR = 1.83, 95% CI: 0.37, 9.09, P = 0.46) showed no significant difference between the HBO and non-HBO groups. Conclusion: The results of this study indicate that HBOT cannot be regarded as an effective measure for the treatment of early-stage necrosis of the femoral head and more large-scale randomized controlled trials are needed for further verification.